PRODUCTION OF NANOMATERIALS FOR APPLICATION AS ADDITIVES - Ospanbekov, E.A.; Paritzan, G.; Ismailov, D.V.; Kerimbekov, D.S. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2020)
This paper presents the results of the obtained carbon nanostructures by the method of arc synthesis in helium. During the synthesis, the methodology for producing fullerene-containing soot was worked out and the yield of fullerenes was increased by 6% at an optimal current of 180 A and a voltage of 30 V, at a vacuum in the reactor of 0.004 Torr, and helium supply of 0.4 kg / cm2, water temperature of the cooling system 19° C, The obtained nanostructures were subjected to purification by evaporation using a Soxhlet apparatus in 5 cycles. Then the obtained fullerenes C60 and C70 were investigated using analytical instruments confirming their presence. After that, the obtained fullerene mixtures were prepared in suspension and tested on a friction and wear machine. During the experiments, the optimal proportions of mixtures of fullerenes with industrial oils I - 40, as well as additives of metal micropowders were selected. The results of the analysis showed that the addition of fillers reduced friction and wear by 3-4%, which improves the effectiveness of additives from previous studies.